Isolation and characterisation of five different hydrophobin-encoding cDNAs from the fungal tomato pathogen Cladosporium fulvum - Segers, G.; Hamada, W.; Oliver, Richard; Spanu, P. (1999)
Five different hydrophobin-encoding cDNA clones from Cladosporium fulvum were isolated from cDNA libraries, made from nutrient-depleted mycelium. One cDNA clone was identical to the previously isolated hydrophobin HCf-1. The other clones were named HCf-2, -3, -4 and -5. HCf-1, -2, -3 and -4 show a high degree of identity, and are predicted to encode class I hydrophobins. HCf-5 encodes a class II hydrophobin. The expression patterns of these hydrophobins at various stages of development, and in liquid media lacking either carbon or nitrogen, or both, showed clear differences. All hydrophobins were more strongly expressed during sporulation than before, with HCf-4 and -5 showing the highest increase. Expression of HCf genes in infected plants was also higher at 16 days than at 10 days after infection. The expression of HCf-5 in sporulating mycelium was much lower in planta than in vitro. All HCf genes were upregulated under conditions of nutrient deprivation. HCf-1, -2, -3 and -4 showed highest levels of transcription in medium lacking both carbon and nitrogen. Expression of HCf-5 was highest in medium lacking nitrogen but containing carbon. HCf-1 was generally the most abundant hydrophobin. The introduction of multiple copies of HCf-1, which caused cosuppression of the endogenous HCf-1 gene, was shown to affect the expression of HCf-2, -3 and -4 also. Expression of HCf-4 was suppressed, but expression of HCf-2 and -3 was upregulated. Expression of HCf-5 was not changed.